2012
DOI: 10.1155/2012/605905
|View full text |Cite
|
Sign up to set email alerts
|

ROS-Mediated Signalling in Bacteria: Zinc-Containing Cys-X-X-Cys Redox Centres and Iron-Based Oxidative Stress

Abstract: Bacteria are permanently in contact with reactive oxygen species (ROS), both over the course of their life cycle as well that present in their environment. These species cause damage to proteins, lipids, and nucleotides, negatively impacting the organism. To detect these ROS molecules and to stimulate the expression of proteins involved in antioxidative stress response, bacteria use a number of different protein-based regulatory and sensory systems. ROS-based stress detection mechanisms induce posttranslationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 50 publications
0
48
0
2
Order By: Relevance
“…In enzymes and signaling proteins found in both prokaryotes and eukaryotes, zinc-binding cysteine-rich regions often serve as sensors of oxidative stress with zinc functioning to inhibit oxidation of key cysteine residues (Maret 2006;Paget and Buttner 2003;Wilcox et al 2001). As is the case with adiponectin in which zinc could slow down disulfide formation but could not prevent it, the thiols coordinating zinc in these zinc-containing redox sensors undergo oxidation resulting in the release of zinc ions (Bonham and Vacratsis 2009;Maret 2006;Ortiz de Orué Lucana et al 2012;Wilcox et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In enzymes and signaling proteins found in both prokaryotes and eukaryotes, zinc-binding cysteine-rich regions often serve as sensors of oxidative stress with zinc functioning to inhibit oxidation of key cysteine residues (Maret 2006;Paget and Buttner 2003;Wilcox et al 2001). As is the case with adiponectin in which zinc could slow down disulfide formation but could not prevent it, the thiols coordinating zinc in these zinc-containing redox sensors undergo oxidation resulting in the release of zinc ions (Bonham and Vacratsis 2009;Maret 2006;Ortiz de Orué Lucana et al 2012;Wilcox et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress is defined as interference in the balance between the production of reactive oxygen species (ROS), including free radicals, oxides and peroxides, and the ability of biological systems to readily detect their presence and detoxify ROS or repair the resulting damage (Ortiz de Orue Lucana et al 2012). In our study, two proteins with high expression levels were identified as catalase (Cat) and superoxide dismutase (Sod), which are the members of antioxidative defense system related to the ROS regulation.…”
Section: Oxidative Responsementioning
confidence: 99%
“…For bacteria, the thiol groups of cysteines in proteins are commonly used as thiol-based switches in redox-sensing regulators to activate specific detoxification pathways and restore the redox balance (1)(2)(3). Direct sensing and quick responses by transcription factors are regarded as an efficient way to promote the survival of a tiny bacterium and overcome oxidation stress (1)(2)(3). In addition, the redox signaling pathways have also been used as important virulence regulators that allow pathogenic bacteria to adapt to the host immune defense system (4).…”
mentioning
confidence: 99%